Providing Consumer Health Information to the Underserved Public at Remote Area Medical Events in East Tennessee. Issue 2 (3rd April 2021) - Petersen, David; Grabeel, Kelsey L.; Lindsay, J. Michael; Watson, Cameron; Dixson, Melanie; Kirkpatrick, Niki; Earl, Martha
ABSTRACT: The University of Tennessee's Preston Medical Library (PML) collaborated with local libraries for outreach at a Remote Area Medical (RAM) event. Librarians staffed a resource table and distributed consumer health handouts, received and fulfilled health information requests, and administered the Newest Vital Sign, a health literacy assessment tool, to volunteers. Researchers analyzed completed health information requests and health literacy assessment results to better inform future outreach. Collaboration at this event built relationships, particularly with the University of Tennessee Knoxville Libraries, for future community events.